Referral and treatment rates of neoadjuvant chemotherapy in muscle-invasive bladder cancer before and after publication of a clinical practice guideline - Miles, Brendan J.W.; Fairey, Adrian S.; Eliasziw, Michael; Estey, Eric P.; Venner, Peter; Finch, Daygen; Trpkov, Kiril; Eigl, Bernhard J. (Canadian Urological Association Journal, 2013)
Introduction: The objective of this study was to compare referral and treatment rates of neoadjuvant chemotherapy for patients with muscle-invasive bladder cancer before and after publication of a clinical practice guideline. Methods: This was a retrospective comparative cohort study of 236 patients diagnosed with clinical stage ≥ T2 bladder cancer in Alberta, Canada. Patients were divided into 2 groups based on the time of diagnosis relative to the publication of the Alberta Genitourinary Oncology Group Clinical Practice Guideline on Bladder Cancer (CPG), which recommends cisplatin-based neoadjuvant chemotherapy for muscle-invasive disease. The pre-CPG group included patients (n = 129) diagnosed prior to publication of the CPG (November 1, 2002 to October 31, 2004, inclusively). The post-CPG group included patients (n = 107) diagnosed after publication of the CPG (November 1, 2005 to October 31, 2007). There was an accrual blackout period of 6 months before and after the CPG release date. The primary analysis compared the two groups with respect to neoadjuvant chemotherapy referral rates, treatment-offered rates and treatment-administered rates. Results: Referral to medical oncology regarding neoadjuvant chemotherapy occurred in 2.3% and 23.4% of patients in the pre- and post-CPG groups, respectively (p < 0.01). Neoadjuvant chemotherapy was offered to 0.8% and 18.7% of patients in the pre- and post-CPG groups, respectively (p < 0.01). Neoadjuvant chemotherapy was administered to 0.8% and 14.0% of patients in the pre- and post-CPG groups, respectively (p < 0.01). Interpretation: Neoadjuvant referral and treatment rates increased after publication of the CPG. However, overall referral and treatment rates remained low, which warrants additional exploration. Introduction : L’objectif de l’étude était de comparer les taux de recommandation et de traitement par chimiothérapie néoadjuvante chez les patients atteints de cancer de la vessie avec envahissement musculaire avant et après la publication d’un guide de pratique clinique. Méthodologie : Il s’agit ici d’une étude comparative rétrospective de cohorte comptant 236 patients de l’Alberta, au Canada, chez qui on avait diagnostiqué un cancer de la vessie de stade clinique T2 ou pire. Les patients ont été répartis en 2 groupes selon que leur diagnostic avait été posé avant ou après la publication du guide de pratique clinique sur le cancer de la vessie (GPC) de l’Alberta Genitourinary Oncology Group, qui recommande une chimiothérapie néoadjuvante à base de cisplatine pour le traitement des cas de cancer avec envahissement musculaire. Le groupe pré-GPC comprenait des patients (n = 129) chez qui le diagnostic avait été posé avant la publication du GPC (du 1er novembre 2002 au 31 octobre 2004, inclusivement). Le groupe post-GPC incluait des patients (n = 107) chez qui le diagnostic avait été posé après la publication du GPC (du 1er novembre 2005 au 31 octobre 2007). Une période cumulative de censure a été calculée 6 mois avant et après la date de publication du GPC. L’analyse préliminaire a comparé les deux groupes quant aux taux de recommandation de la chimiothérapie néoadjuvante, aux taux d’offre et d’administration du traitement. Résultats : La chimiothérapie néoadjuvante a été recommandée chez 2,3 et 23,4 % des patients dans les groupes pré-GPC et post-GPC, respectivement (p < 0,01). Elle a été offerte à 0,8 % et 18,7 % des patients de ces mêmes groupes (p < 0,01), et administrée à 0,8 et 14,0 % des patients des groupes pré-GPC et post-GPC, respectivement (p < 0,01). Interprétation : Les taux de recommandation et de traitement concernant la chimiothérapie néoadjuvante ont augmenté après la publication du GPC, mais sont tout de même demeurés faibles, ce qui nécessite une analyse plus poussée.